Needs Satisfaction Effect on Exercise Emotional Response: A Serial Mediation Analysis with Motivational Regulations and Exercise Intensity - Diogo Santos Teixeira; António Labisa Palmeira
Abstract Regarding psychological responses to exercise, this study aimed to analyze the mediating effects of motivational regulations and intensity in the association between basic psychological needs satisfaction and emotional responses. This was a cross-sectional study of 495 health club members (M = 40.50 years; SD = 13.54); of these, 186 were women (37.6%) and 309 men (62.4%), with an average attendance of 2.61 sessions per week (SD=1.29). Self-determination theory motivational regulations and basic psychological needs (BPN), perceived exercise intensity, and emotional response were measured. Serial mediation procedures were followed to test the interactions of variables. Models with autonomous regulations predicted positive emotional responses. As for the negative emotional response, the models with external regulation presented the highest predictions for negative activation. Results indicate that BPN satisfaction is associated with better emotional response, partially explained by autonomous regulations and perceived exercise intensity. In externally regulated individuals, perceived exercise intensity appears to be important to sustain a better emotional response.